Modeling the Open Unemployment Rate of Regency/City in West Java Province in 2021 using Spatial Autoregresive Moving Average and Spatial Durbin Model - hermalia, Lia (Journal of Statistics and Data Science, 2023)
The Open Unemployment Rate is an important indicator to see the non-absorption of labor by the labor market. According to statistic indonesia, in August 2021, the Open Unemployment Rate in Indonesia was 6.49% or around 9.1 million people a population of 50 million, West Java Province has a high unemployment rate, reaching 9.82%. When examined, the open unemployment rate in West Java tends to cluster higher in the west and lower in the east, indicating that there are spatial factors in the data. Therefore, an analysis was conducted involving the variables of Labor Force Participation Rate, Expected Years of Schooling, and Expenditure per capita as independent variables in measuring their influence on the Open Unemployment Rate, the methods used Spatial Autoregressive Moving Average and Spatial Durbin Model. The result shows that both methods are significant in all tests conducted, then the best method is chosen by comparing the AIC value, it is obtained that the best method in modeling the Open Unemployment Rate in West Java Province is the Spatial Durbin Model with Rsquared of 81.32%. Indicating that the independent variables have a significant effect of 81.32% while 18.68% is influenced by other variables not examined.